Bitcoin vs Mutual Funds : which is more profitable? - Siti Epa Hardiyanti (Jurnal Ilmu Keuangan dan Perbankan (JIKA), 2025)
The phenomenon of increasing public interest in investing in crypto assets, especially Bitcoin, has raised major questions about its feasibility and profitability compared to conventional investment instruments such as mutual funds. This study aims to compare the profitability and risk levels between Bitcoin as a cryptocurrency asset and mutual funds as traditional financial instruments. Although Bitcoin has gained increasing popularity as an alternative investment, there remains a lack of empirical research directly comparing its performance with mutual funds over an equivalent time horizon. Using a quantitative approach, this study analyzes historical monthly data from 2015 to 2024. Metrics such as cumulative return, average monthly return, CAGR, Sharpe Ratio, and maximum drawdown were employed to evaluate the performance of both instruments. Positioned within the existing literature on asset comparison, this study offers a novel empirical contribution by directly contrasting Bitcoin and mutual funds through risk-return analysis. The findings reveal that while Bitcoin offers significantly higher returns, it also carries much greater volatility and drawdown risk. These insights serve as a practical foundation for designing investment strategies aligned with different investor risk profiles. The research contributes to the body of knowledge in portfolio management and data-driven investment decision-making.   Keywords: Bitcoin, mutual funds, risk-return, volatility, investment performance, portfolio management